Accompanied by a Believing Wife : Ministry and Celibacy in the Earliest Christian Communities - Collins, Raymond F., 1935- (Book collections on Project MUSE., 2013)
What light does the New Testament shed on the practice of celibacy for the sake of the kingdom? In his newest work, renowned Scripture scholar Raymond F. Collins turns his attention to the question, which of course has important implications for the church in our own day. Though the answer is not a simple one, and it does not necessarily translate automatically into clear contemporary ecclesial policy, it still serves as an important foundation for discussion. Collins gives careful consideration of the methodology to be used in approaching the question and to important aspects of the sociocultural context of first-century Palestine within which the New Testament took form. He then explores what Jesus said to the disciples, several disciples' own statuses as married men, and Paul's teaching and personal example on marriage.